To Study the Impact of Teachers’ Quality Education on Students’ Performance at Intermediate Level in District Sialkot - Fayiza Parveen; Muhammad Sarwar; Muhammad Arif (Journal of Management Practices, Humanities and Social Sciences, 2024)
The quality of education that teachers impart decides the academic performance of students. This research article investigates how quality education teachers provide improves teaching ability and quality, benefiting intermediate-level students in District Sialkot. A structured questionnaire is administered to 200 students from public and private colleges. To estimate the influence of teachers' educational level, pedagogical skills, and professional development on student's academic outcomes, we used descriptive statistics research methods with statistical indices (on aggregated data) along with correlation study and regression analysis. In addition, students' success is highly correlated to each teacher's educational quality. Hence, during a time when there are increasingly stringent curriculum standards and new teaching methods that have just been introduced. Results from this study indicate that investments in improving teacher quality through direct targeted training programs lead to substantial gains at the intermediate level. The study has important implications for policymakers and educators looking to improve educational outcomes in the region. The research also suggests how long-term teacher efficacy develops the quality and professional development of students’ achievements. Furthermore, it is also important to highlight the role of investigating the performance of digital tools and resources to improve the quality of education, particularly in the light of emphasising the quality of education in the context of the academic landscape. These revelations may provide insightful directions for upcoming projects that try to enhance teaching methods for quality student outcomes.